STRATEGI PEMASARAN UNTUK MENINGKATKAN OMZET PENJUALAN PADA TOKO DUO SISTER HIJAB KOTA BENGKULU - Annisa Murti; Sri Ekowati (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2020)
Sister Duo Hijab store is a company engaged in fashion which produces and markets hijab, clothes, pants, hijab shirts, tuspins etc. This business has been running for 3 years and is growing well but has many competitors in the same field. This study is entitled "analysis of marketing strategies to increase sales in the city of Bengkulu hijab duo sister shop". This research is based on the importance of marketing strategies in an organization. This study also aims to determine the company's internal and external factors, determine the company's position and determine the right marketing strategy for the company to increase sales. The analysis technique used is the SWOT analysis in which the analysis tools are IFAS and EFAS matrices. There are 2 informants in this study, namely the owner and marketing manager and the owner and financial manager. data collection techniques using interviews, observation and documentation. The total score from the analysis of internal factors was 3.85 with a strength of 3.15, a weakness of 0.70. Meanwhile, the total score of external factors is 2.40 with a 1.95 chance, a threat of 0.45. Whereas IFAS and EFAS matrix position of the company is in quadrant 1, which is an aggressive strategy. By using the SWOT analysis technique, the results of this study can be concluded that the strengths with the largest score are good product quality, weaknesses namely narrow parking spaces, opportunities namely technological development and threats namely intense competition.